Brand Loyalty And Consumer Engagement In The Indian Market: A Comparative Study Of Local And Global Brands - Dr Madhura Shukla (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
In the vibrant and diverse Indian market, brand loyalty and consumer engagement play pivotal roles in shaping competitive strategies for both local and global brands. This comparative study aims to explore and analyze the factors influencing brand loyalty and consumer engagement, drawing distinctions between local and global brands operating in India.The research employs a mixed-methods approach, combining qualitative interviews with consumers and quantitative surveys across urban and rural demographics. Qualitative methods delve into consumer perceptions, attitudes, and emotional connections towards brands, while quantitative surveys measure factors such as purchase intention, brand trust, and satisfaction levels.